Innovative Approaches And Master-Disciple Traditions In Traditional Singing (Texas Journal of Philology, Culture and History, 2024)
The article is devoted to the topic “Innovative approaches and teacher-student traditions in traditional singing”, which discusses the importance of using modern technologies in traditional singing education and preserving the ancient teacher-student system. The article considers ways to increase the effectiveness of young singers' education by using new pedagogical and technological approaches based on teacher-student traditions. It is also emphasized that by integrating these two approaches, Uzbek traditional music can be studied and developed more deeply by future generations. At the same time, the article highlights the creative potential and new opportunities for music education that arise as a result of the combination of traditional and modern methods.